2004
DOI: 10.1111/j.1095-8312.2004.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome downsizing in polyploid plants

Abstract: All else being equal, polyploids are expected to have larger C-values (amount of DNA in the unreplicated gametic nucleus) than their diploid progenitors, increasing in direct proportion with ploidy. This expectation is observed in some polyploid series, especially those newly formed, but there are examples suggesting that C-values in particular polyploids are less than expected. The availability of the Angiosperm DNA C-values database (http:// www.rbgkew.org.uk/cval/homepage.html) has allowed this question to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
424
6
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 613 publications
(459 citation statements)
references
References 91 publications
25
424
6
4
Order By: Relevance
“…In our study, we confirmed a general trend of genome downsizing in polyploids with respect to their diploid progenitors (Leitch and Bennett 2004). This contrasts with the closely related genus Pilosella, where downsizing was not apparent in triploids, but only at higher ploidy levels (Suda et al 2007).…”
Section: Genome Size Variation and Its Geographical Patternsupporting
confidence: 83%
See 1 more Smart Citation
“…In our study, we confirmed a general trend of genome downsizing in polyploids with respect to their diploid progenitors (Leitch and Bennett 2004). This contrasts with the closely related genus Pilosella, where downsizing was not apparent in triploids, but only at higher ploidy levels (Suda et al 2007).…”
Section: Genome Size Variation and Its Geographical Patternsupporting
confidence: 83%
“…This contrasts with the closely related genus Pilosella, where downsizing was not apparent in triploids, but only at higher ploidy levels (Suda et al 2007). Several mechanisms may lead to genome size reduction in polyploids: (1) unequal homologous recombination, (2) elimination of specific DNA sequences (including sequences in low-and high copy number from both coding and non-coding regions), and (3) change in transposons activity (Leitch and Bennett 2004).…”
Section: Genome Size Variation and Its Geographical Patternmentioning
confidence: 91%
“…One proposed mechanism is the loss of whole chromosomes or genes following polyploidization events (Leitch and Bennett 2004). But our data reveal no correlation between chromosome number and genome size from an evolutionary perspective.…”
Section: Mechanisms Of Change In Genome Sizecontrasting
confidence: 64%
“…Ranunculus lingua, the species with the largest genome size among those studied in this paper, is likely a high polyploid, as its commonest chromosome The two taxa for which two populations were studied also could likely present different ploidy levels. For Caltha palustris, 2C-values (19.54 and 19.62 (Leitch and Bennett 2004). One of the previous records from this taxon (2C = 4.20, 11.05 pg; Table 1) would suggest still one more ploidy level.…”
Section: Genome Size and Ploidy Levelmentioning
confidence: 72%